Myomectomy in infertile women: More harm than good? - Mercorio, Antonio; Della Corte, Luigi; Boccia, Dominga; Palumbo, Mario; Reppuccia, Sabrina; Buonfantino, Cira; Cuomo, Lara; Borgo, Maria; Zitiello, Antonio; De Angelis, Maria Chiara; Laganà, Antonio Simone; Bifulco, Giuseppe; et al. (Frontiers in Surgery, 2023)
Adhesions formation following gynecological surgery remains a challenge. The adoption of minimal invasive surgical approaches such as conventional or robotic-assisted laparoscopy combined with meticulous microsurgical principles and the application of adhesion –reducing substances may reduce the risk of de novo adhesion formation but do not eliminate it entirely. Myomectomy is the most adhesiogenic surgical procedure and postoperative adhesions following it, could have a significantly impact on the ability to conceive, therefore several considerations should be taken into account when surgery is performed for fertility enhancement. Since the impact of fibroids on reproductive function is controversial, an adequate evaluation whether the benefits outweigh the surgical risk is needful. Among several factors,the size and location of fibroids are the most accountable factors in terms of adhesion production and development of secondary infertility; therefore the search for effective strategies against adhesion formation in this setting is required . Purpose of this paper is to review the incidence and factors of adhesion formation and the current best preventive measures.